An Improved Design Of Piezoelectric Raindrop Energy Harvester - Wong, Chin Hong (2017)
Raindrop energy harvesting provides a good energy resource that can be applied in rainy environments. While extensive research has been investigated on raindrop energy harvesting by using piezoelectric mechanism, a higher efficiency of piezoelectric raindrop energy harvester (PREH) are still in on-going research. This research study presents design and development of an improved design of PREH. In order to achieve the desired improved design, several steps have been conducted. This includes investigation on the raindrop profiles to predict the kinetic energy in a falling droplet. It was found that the total kinetic energy depends on the droplet sizes and fall velocities. Secondly, an experiment was conducted to compare the performances of commonly used commercial PVDF transducers which are bridge and cantilever structures which were subjected to simulated raindrops. Experimental results showed that, the bridge structure transducer with dimension of 30 mm × 4 mm × 25 μm generated higher open-circuit voltage than cantilever structure, which is 4.22 V and 0.41 V, respectively. The next step is the Finite Element Method (FEM) analysis through COMSOL Multiphysics software to investigate open-circuit voltage, charge density, deflection of transducer, and resonance frequency. Based on the bridge structure, various types of modified structures; S-shaped, zigzag-shaped, H-shaped, and X-shaped transducers were further investigated via FEM simulation. Based on the simulation results, the optimum structure of PREH is the six-spoke wagon wheel structure which is modified from X-shaped. It generated 63.85% higher voltage and 223.42% higher charge density than the basic bridge structure transducer. Therefore, the six-spoke wagon wheel transducer is selected to be fabricated. The fabricated PVDF transducer is also validated and characterised by X-ray diffraction (XRD) and Fourier transform infrared spectrometer (FTIR) measurements. The ezoelectr c constant was enhanced to 7 C/N and the β-phase content was improved to 57.8% by corona poling process. The fabricated transducer generated DC voltage of 22.5 mV and electrical power of 15.3 nW as impacted by actual raindrops. Based on simulation results, the performance for six-spoke wagon wheel structure is better than the bridge structure. However, the experimental results showed the other way. This is due to the piezoelectric constant, d33, for the fabricated transducer (7 pC/N) is lower than commercial transducers (16 pC/N). The discrepancy of the value of the d33 is due to the limited poling voltage in the poling apparatus. In overall, the research has successfully investigated an improved design of PREH through simulation and experimental. Although the power is considerably small, it is proven that the raindrop energy would be a promising approach in energy harvesting application.